2012
DOI: 10.1073/pnas.1112171109
|View full text |Cite
|
Sign up to set email alerts
|

Protein-binding dynamics imaged in a living cell

Abstract: Historically, rate constants were determined in vitro and it was unknown whether they were valid for in vivo biological processes. Here, we bridge this gap by measuring binding dynamics between a pair of proteins in living HeLa cells. Binding of a β-lactamase to its protein inhibitor was initiated by microinjection and monitored by Förster resonance energy transfer. Association rate constants for the wild-type and an electrostatically optimized mutant were only 25% and 50% lower than in vitro values, whereas n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
116
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 39 publications
10
116
0
Order By: Relevance
“…4b; the population of nonspecific complexes (dRMS >5 Å) is enhanced as the proteincrowder attraction strength increases. These findings are also consistent with recent experimental results (Phillip et al 2012). …”
Section: Effects Of Mixed Macromolecular Crowdingsupporting
confidence: 94%
“…4b; the population of nonspecific complexes (dRMS >5 Å) is enhanced as the proteincrowder attraction strength increases. These findings are also consistent with recent experimental results (Phillip et al 2012). …”
Section: Effects Of Mixed Macromolecular Crowdingsupporting
confidence: 94%
“…We want to emphasize that there are other crowding-agent studies not reported on here, for example on the role of crowding on enzymatic activity (Vopel and Makhatadze 2012), protein-protein association (Phillip et al 2012), and mixtures of crowding agents (Batra et al 2009). Our in vitro/in silico studies, in combination with work by others, underscore that macromolecular crowding results in: (1) more stable proteins, (2) faster and more homogeneous folding kinetics, and (3) population shifts of conformational ensembles.…”
Section: Discussionmentioning
confidence: 96%
“…Flory-Huggins theories as used here might thus provide novel insights into the demixing of multicomponent polymeric systems (41). An interesting next step will be a direct comparison of experiments in vitro with intracellular measurements (14,26), and the required quantitative tools are beginning to emerge (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%